Computed Tomograpic Studies On Sphenoid Sinus Variants - VIMAL KUMAR M; SURESH SUKUMAR; DR. MAMATHA.H (International Journal of Pharma and Bio Sciences, 2012)
The sphenoid sinus is deeply seated in the skull and is the most inaccessible paranasal sinus intimately related to numerous vital neural and vascular structures. This work determines the incidence of the anatomical variations of sphenoid sinus reviewed by the CT scan and their impact on related neurovascular structures, for the safe removal of intersphenoidal and pituitary lesions and the Endoscopic Endonasal Transsphenoidal Aproach (EETA) to treat sellar, parasellar,and suprasellar tumours. The CT scan of 80 patients were reviewed regarding the different anatomical variations of the sphenoid sinus: degree of pneumatisation, protrusion of internal carotid artery (ICA) and optic nerve (ON), and dehiscence of the walls of ICA and ON, and the septation pattern. We found 42 cases showing protrusion and 13 cases with dehiscence of bony wall on ICA. 51 cases showing protrusion and 18 cases showing dehiscence on bony wall of optic nerve. Regarding the pneumatisation of sphenoid sinus, the major type found were of sellar in 62.5%, 25% of cases with presellar, and 15% were of post sellar pneumatisation. The different anatomical configuration of sphenoid sinus is important for adequate treatment of its disease.